2020
DOI: 10.3389/fpubh.2020.563573
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Social Exclusion Framework to Explore the Relationship Between Sudden Unexpected Deaths in Infancy (SUDI) and Social Vulnerability

Abstract: Background: Sudden Unexpected Death in Infancy (SUDI) is a leading cause of preventable infant mortality and strongly associated with social adversity. While this has been noted over many decades, most previous studies have used single economic markers in social disadvantage analyses. To date there have been no previous attempts to analyze the cumulative effect of multiple adversities in combination on SUDI risk.Methods: Based on sociological theories of social exclusion, a multidimensional framework capable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…While this has worked in certain contexts, it has failed those from lower socioeconomic groups. 32 Context certainly played a role in the success of the original ‘Back To Sleep campaign’, which took place when parental and societal concern about SIDS was high; deaths occurred across socioeconomic groups; and high profile cases in the UK brought public awareness of the risks and prevention strategies. 33 Targeting those with more complex barriers to adopting messages is where our greatest challenge now lies.…”
Section: Discussionmentioning
confidence: 99%
“…While this has worked in certain contexts, it has failed those from lower socioeconomic groups. 32 Context certainly played a role in the success of the original ‘Back To Sleep campaign’, which took place when parental and societal concern about SIDS was high; deaths occurred across socioeconomic groups; and high profile cases in the UK brought public awareness of the risks and prevention strategies. 33 Targeting those with more complex barriers to adopting messages is where our greatest challenge now lies.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in post-neonatal mortality could be achieved by increasing support for caregivers, optimising the environments that infants are raised in and reducing risk factors for adverse events. For example, breast feeding support, improved access to mental health services and financial support for infant-care essentials could improve the environments that infants are raised in [4], whilst individually tailored or community-based interventions to address risk factors such as smoking and sleeping position, could reduce the risk of sudden unexpected deaths in infancy (SUDIs) amongst the most socially vulnerable groups [26].…”
Section: Implications For Public Health Practicementioning
confidence: 99%
“…For example, several enrolled families reported experiencing housing challenges during the study, including housing in disrepair (such as broken plumbing, windows), unresponsive landlords, lack of affordable housing, and eviction. This finding reinforced the necessity of providing a broad array of resources to families living in under-resourced neighborhoods and emphasized the need for tailored interventions that can help respond to a caregiver’s highest priorities and unique circumstances, concerns, and needs [ 15 , 21 , 22 , 23 , 24 , 28 , 30 , 31 , 51 ].…”
Section: Discussionmentioning
confidence: 90%
“…Research has suggested the need for tailored interventions that respond to a caregivers’ unique circumstances, concerns, and needs, especially among families that are living in under-resourced neighborhoods [ 15 , 21 , 22 , 23 , 28 , 30 , 51 ]. To tailor their responses to specific family needs, MBS coaches ask families about perceptions and reasons behind infant sleep practices.…”
Section: Methodsmentioning
confidence: 99%